Zgoda małżeńska jako przyczyna sprawcza małżeństwa - Smoliński, Tomasz (Ius Matrimoniale, 2019)
The article presents the issue of marital consent as the causative cause of marriage, taking into account the genesis of the problem and the diversity of views over the centuries and depending on culture. The article presents an outline of the genesis of the problem, taking into account different cultures, then the author focused on the history of marital consent in Christian culture, in order to move on to the current teaching of the Catholic Church in relations to marital consent, including marital love as an element of consent and completion of the marriage as a prerequisite for entering into a valid marriage.